Utilizing Ultra-High Performance Concrete Overlay for Road Pavement Repair and Strengthening Applications - Lay Boon Tan; Milad Hafezolghorani; Azman Mohamed; Khaled Ghaedi; Yen Lei Voo (Advances in Technology Innovation, 2023)
This study aims to develop a new thixotropic ultra-high-performance concrete (UHPC) overlay for the repair and strengthening of damaged hot mix asphalt (HMA) pavements. The overlay is purposely designed to accommodate the roadway slope of up to 10% due to presence of viscosifying agent materials. The original UHPC materials are comprised of granite aggregate, ultra-fine calcium carbonate, shrinkage-reducing admixture, viscosifying agent, and expansive agent. The study is conducted with three sets of samples provided and considers thixotropic and mitigated shrinkage properties through comparing control (non-thixotropic) overlay 1 (thixotropic), and overlay 2 (thixotropic) mixtures. Based on the obtained results, only overlay 1 corresponds to the minimum requirement for pavement rehabilitation, with 160-200 mm flowability and -545.3 µm/m free shrinkage. As a result, an average 50 mm thick overlay 1 is selected to repair a damaged HMA pavement (1800 m2), while the field implementation procedures and drawing details are also presented in this paper.